2011
DOI: 10.1590/s1415-43662011000100011
|View full text |Cite
|
Sign up to set email alerts
|

Fertilidade do solo e nutrição de tangerineiras ‘Ponkan’ manejados com resíduos sólidos e adubação química

Abstract: RESUMOO objetivo do trabalho foi avaliar alguns atributos químicos do solo e o estado nutricional das tangerineiras 'Ponkan' no solo manejado com resíduos orgânicos e adubação química. O experimento foi conduzido no Departamento de Recursos Naturais/Ciência do Solo -FCA/UNESP em Botucatu, SP. As mudas de tangerineira foram plantadas e manejadas com lodo de esgoto (LE), esterco de curral curtido (EC) e adubação química (AQ). Os resultados permitiram concluir que houve um aumento significativo nos teores dos atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
4
0
3
Order By: Relevance
“…This increase is attributed to the organic nature of the residue, and its effects have been widely reported in the literature (Simonete et al, 2003;Galdos et al, 2004;Nascimento et al, 2004;Barbosa et al, 2007;Nascimento et al, 2009;Prates et al, 2011;Santos et al, 2011). It should be pointed out that the increase in organic matter in soils fertilized with sewage sludge is more effective in the incorporation layer, as observed by Galdos et al (2004) in a eutroferric Red Latosol cultivated with corn and fertilized with two sewage sludge applications in two crop years.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…This increase is attributed to the organic nature of the residue, and its effects have been widely reported in the literature (Simonete et al, 2003;Galdos et al, 2004;Nascimento et al, 2004;Barbosa et al, 2007;Nascimento et al, 2009;Prates et al, 2011;Santos et al, 2011). It should be pointed out that the increase in organic matter in soils fertilized with sewage sludge is more effective in the incorporation layer, as observed by Galdos et al (2004) in a eutroferric Red Latosol cultivated with corn and fertilized with two sewage sludge applications in two crop years.…”
Section: Resultsmentioning
confidence: 75%
“…The results showed that sewage sludge application influenced the increase in organic matter contents in the layer of 0-5 cm. Santos et al (2011) also reported that sewage sludge fertilization in 'Ponkan' mandarin promoted significant increment in the values of soil organic matter only in the layer of 0-20 cm. However, Backes et al (2009) observed no positive effect of the application of different sewage sludge doses in castor bean cultivation on the increase of soil organic matter contents.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Nota-se que as folhas das plantas adubadas com lodo de esgoto apresentam valores superiores à adubação convencional nos teores de N, P, Ca e S. Os valores de K e Mg não são influenciados pelo lodo de esgoto. Quanto aos teores de As, Cd, Cr e Hg, não há toxidez (SANTOS et al 2011).…”
Section: Lodo De Esgoto Na Produção De Alimentosunclassified
“…Plantas cítricas manejadas com adubações químicas e com resíduo orgânico resultaram em benefícios na nutrição, produtividade e qualidade de frutas (MATTOS JÚNIOR et al, 2004;SANTOS et al, 2011;MATTOS JÚNIOR;BOARETTO, 2011). No entanto, ainda são escassos experimentos em campo que avaliem esses fatores com a aplicação de produtos com algas calcárias em pomares cítricos.…”
Section: Introductionunclassified